Effect of radiation with temperature dependent viscosity and thermal conductivity on unsteady a stretching sheet through porous media - Abdou, M. M. M. M. M. (Nonlinear Analysis: Modelling and Control, 2010)
A numerical model is developed to study the effect of thermal radiation on unsteady boundary layer flow with temperature dependent viscosity and thermal conductivity due to a stretching sheet in porous media. The Rosseland diffusion approximation is used to describe the radiative heat flux in the energy equation. The governing equations reduced to similarity boundary layer equations using suitable transformations and then solved using the Runge–Kutta numerical integration, procedure in conjunction with shooting technique. A parametric study illustrating the influence of the radiation R, variable viscosity ε, Darcy number Da, porous media inertia coefficient γ, thermal conductivity κ and unsteady A parameters on skin friction and Nusselt number.